ANALISIS KINERJA BOILER DI PT. PLN (PERSERO) WILAYAH KALIMANTAN SELATAN KALIMANTAN TENGAH SEKTOR PLTU ASAM - ASAM - Jenta Yudi Perageminisko; Aqli Mursadin (Universitas Lambung Mangkurat, 2019)
Boiler is a tool that serves to convert water into pressurized steam. In the heat causes heat boiler heat transfer through the water into pressurized steam that is heated from the fuel in the furnace.And often a problem of burning in the boiler is less than the maximum. Because the incoming energy is energy derived from the fuel, there is some energy lost during the combustion process it happens because the fuel has a low heat so that the combustion is not maximal cause the boiler performance is reduced. To avoid this, it is necessary to maintenance for the boiler component in order to improve performance. Direct method is